ESTRATEGIA DE MARKETING SOCIAL PROPUESTA EN LA COMUNIDAD RURAL VIVERO - Gladys Caridad Seguí León, Hany Raisely Pérez Bruno (Fonseca, Journal of Communication, 2023)
With the creation of The Houses of Orientation to the Woman and the Family (COMF) in the Federation of Cuban Women (FMC) in the year 1990, a new stage of attention began to the woman and the Cuban family, offering consultantship and he/she helps on diverse topics as drogadicción, domestic violence, alcoholism, etc.